1990
DOI: 10.1002/polb.1990.090280915
|View full text |Cite
|
Sign up to set email alerts
|

A fourier‐transform infrared spectroscopic study of the surface hydrolysis of polythiazyl

Abstract: SynopsisThe hydrolysis of ( SN), in air at room temperature and 90% relative humidity has been studied using the attenuated total reflectance ( ATR) method. Decomposition gave rise to strong bands at 3210 and 3150 cm-' [ v3 and v1 (NH:)], 1420 cm-' ( v b NH:), 1220 cm-' ( S = O ) , 1089 and 610 cm-' [ u1 and v3 ( S O : -) ] . For the first 3 days, the decay of the 808 and 690 cm-' bands of (SN), was first order, with a half life of about 30 h. The spectroscopic data were consistent with the rapid formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They found that the process occurred slowly, probably via ±NHSO 2 ±NH 2 and S=NH end groups, to give ammonium sulfate and sulfur. [60] X-ray photoelectron spectra show that (SN) x films prepared from (NSCl) 3 ±Me 3 SiN 3 are more readily attacked by moist air than those prepared from S 2 N 2 . [13] The current± voltage curves of junctions between (SN) x films and various metals (e.g., Ag, Cu, Zn) suggest that semiconducting metal sulfides are formed at the interface.…”
Section: Chemical Stabilitymentioning
confidence: 96%
“…They found that the process occurred slowly, probably via ±NHSO 2 ±NH 2 and S=NH end groups, to give ammonium sulfate and sulfur. [60] X-ray photoelectron spectra show that (SN) x films prepared from (NSCl) 3 ±Me 3 SiN 3 are more readily attacked by moist air than those prepared from S 2 N 2 . [13] The current± voltage curves of junctions between (SN) x films and various metals (e.g., Ag, Cu, Zn) suggest that semiconducting metal sulfides are formed at the interface.…”
Section: Chemical Stabilitymentioning
confidence: 96%
“…17−25 Unfortunately, its applications are limited due to its unstable nature that leads to degradation in water or under atmospheric conditions to give a gray powder. 2,3,12,17,26,27 Although a large diversity of small organic compounds containing sulfur−nitrogen bonds have been studied for their biological activities 4,28−48 and synthesis of transition-metal complexes, 49−52 surprisingly few polymers possess nitrogen−sulfur bonds along the backbone. 30,53,54 We recently reported the synthesis of polysulfenamides, polydiaminosulfides, and polydiaminodisulfides, but these polymers possess sp 3 hybridized carbon atoms along their backbones that interrupt conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…Polythiazyl (SN) x was first synthesized in 1906 and contains alternating sulfur and nitrogen atoms along its backbone (Figure ). It has many interesting properties such as being one of only two examples of a synthetic polymer that is metallic at room temperature under atmospheric pressure and in the absence of doping. This polymer is also superconducting with a critical temperature of 0.3 K. Unfortunately, its straightforward composition does not lead to simple methods to alter its structure or properties, most research has described doping with different chemicals. This polymer has been heavily investigated since its discovery, and different methods to synthesize it and its derivatives have been developed as well as numerous potential applications that take advantage of its electrical conductivity through the alternating sulfur–nitrogen bonds. Unfortunately, its applications are limited due to its unstable nature that leads to degradation in water or under atmospheric conditions to give a gray powder. ,,,,, Although a large diversity of small organic compounds containing sulfur–nitrogen bonds have been studied for their biological activities , and synthesis of transition-metal complexes, surprisingly few polymers possess nitrogen–sulfur bonds along the backbone. ,, We recently reported the synthesis of polysulfenamides, polydiaminosulfides, and polydiaminodisulfides, but these polymers possess sp 3 hybridized carbon atoms along their backbones that interrupt conjugation. ,,,…”
Section: Introductionmentioning
confidence: 99%